Efektivitas Penerapan Absensi Fingerprint Terhadap Kedisiplinan Kerja Pegawai Dilingkungan Sekretariat Daerah Kota Madiun - Siti Rokhayah; Ahadiati Rohmatiah; Mutmainah Mutmainah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2021)
Background – Supervision of employees needs to be done optimally in order to achieve company goals. Supervision of employee attendance due to frequent absenteeism requires company action to be able to discipline employees. For example, the use of a fingerprint attendance machine in the Madiun City Regional Secretariat. Purpose – To know about the effect of effectiveness of fingerprint attendance application on employee discipline as measured using practical dimensions, accurate dimensions, and security dimensions. Design/ Methodology/ Approach – This research is quantitative research. The samples in this research are all of Madiun City Regional Secretariat employee. Their fingerprints have been recorded by the company. They numbered 159 people. Sampling technique use saturated sample. Data analysis in this research use multiple linier regression analysis. Result and discussion – This research result show that practical dimension, accurate dimension, and security dimension effect to discipline of work employee, partially and simultaneously in the Madiun City Regional Secretariat. Accurate dimension is dominant variable. Research Implication - The results of this study can be used as a reference in conducting performance appraisals and employee supervision. Limitations - This research was conducted at the Madiun City Regional Secretariat and is devoted to employees whose fingerprints have been registered on the fingerprint attendance machine.